Association of digit ratio (2D:4D) with world rankings in female fencers - Bescos, R.; Esteve, M.; Porta, J.; Mateu, M.; Iglesias, X.; Irurtia, A.; Voracek, M. (Archivos de medicina del deporte, 2008)
The digit ratio between the second and the four fingers (2D:4D) is a widely studied putative marker of prenatal androgen levels while the absolute finger length is a putative marker of pubertal-adolescent androgen levels. In order to study the prenatal programming of sporting success, it has been investigated the associations of the 2D:4D ratio and absolute finger length with sport performance The sample used to develop the research was composed by 87 female world-class épée fencers. After receiving participants` informed consent, their name, nationality, age, height, weight, fencing hand, duration of international career (years of attendence of world cup competitions), and current and highest past world rankings were recorded. Following standard practice, length of index fingers (2D) and ring fingers (4D) was measured from palmar-view photocopies of athletes` right (R) and left (L) hands by two trained, mutually blinded investigators, using digital vernier calipers measuring to 0.01 mm. Results show that lower (masculinized) 2D:4D significantly corresponds to better current as well as highest past world rankings, when the associations are controlled for the most salient factors (height, weight, and years of international experience) for the rankings in this sample. Longer (masculinized) fingers also are associated with world rankings, but these effects are attenuated to insignificance in the same three controls. This pattern of results may suggest that, for sporting success, prenatal hormonal influences have predominance over pubertal-adolescent ones. Supplemental findings include a much higher prevalence of left-handedness in this sample of elite athletes, relative to the female general population, and slightly lower (more male-typed) 2D:4D and better world rankings in left-handers than in right-handers. These findings add to evidence for sex-hormonal prenatal programming of aptitude across a variety of sports